SNP-based genetic linkage mapping and whole-genome diversity assessment in cassava (Manihot esculenta Crantz) accessions from Africa and Latin America - Myburg, Alexander Andrew (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.